Teleology, first principles, and scientific method in Aristotle's biology - Gotthelf, Allan, 1942- (Oxford : Oxford University Press, 2012)
This volume draws together Allan Gotthelf's pioneering work on Aristotle's biology. He examines Aristotle's natural teleology the axiomatic structure of biological explanation, and the place of classification in the three great works with which Aristotle laid the foundations of biological science.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Aristotle; Biology -- Philosophy